Efektivitas Pemanfaatan Dana Klaim Asuransi Usahatani Padi (AUTP) di Subak Sengempel, Desa Bongkasa, Kecamatan Abiansemal Kabupaten Badung - ANAK AGUNG ARISTA SATWIKANI; I GUSTI AYU AGUNG AMBARAWATI; I DEWA GEDE RAKA SARJANA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
Effectiveness Of Utilization Of The Rice Crop Insurance (AUTP) Claims Fund atSubak Sengempel, Bongkasa Village, Abiansemal District Badung Regency AUTP was launched by the government as an effort to protect farmers from crop failureby providing claims that can be used as capital for the next season. This research aimsto determine the response of farmers and the effectiveness of AUTP claims fundutilization. The research was done purposively in Subak Sengempel, Bongkasa Village,Abiansemal Sub-district of Badung Regency. Samples were 62 farmers who receivedclaims fund. Data were collected through interviews, observation and documentation.Data analysis is descriptive qualitative and quantitative. The results shows that farmersrespond positively to the AUTP program in terms of knowledge and attitude. Theaverage knowledge of farmers reached 80% of the total expected knowledge aboutAUTP and the farmer's attitude were agreed with the average score is 4.10. Furthermore,by type of fund usage is effective category which is 90.32% of farmers use as a capitalfor rice cultivation for the next planting season. The utilization of AUTP claims fundsviewed from the claims capability is effective to cover 110.31% cost of farmingproduction per 0.25 ha up to planting and maintenance stages. In this research can besuggested the AUTP program needs to be continued and coordination between theparties involved should be maintained.